Role of Albumin as a Nutritional and Prognostic Marker in Elective Intestinal Surgery. (13th April 2020) - Galata, Christian; Busse, Linda; Birgin, Emrullah; Weiß, Christel; Hardt, Julia; Reißfelder, Christoph; Otto, Mirko
Abstract : Background . The aim of this study was to investigate albumin, nutritional status, and inflammation in the perioperative course of patients undergoing elective intestinal surgery. Methods . A retrospective analysis of patients with preoperative measurements of nutritional parameters who underwent intestinal surgery between April 2017 and August 2018 at our institution was performed. Preoperatively, the correlation of albumin levels with markers for inflammation and nutritional status was investigated. Postoperatively, albumin levels were assessed with regard to high-grade morbidity and inflammation. Results . A total of 105 patients were included. Preoperatively, albumin levels were correlated with both markers for nutritional status and inflammation, with phase angle (PA) (p = 0.004 ) and C-reactive protein (CRP) (p < 0.001 ) as independent factors predicting the albumin levels in multivariable analysis. Postoperatively, the reduction in serum albumin (∆-albumin) on postoperative day (POD) 1/2 (p = 0.025 ) and POD 4/5 (p = 0.003 ) was significantly associated with Clavien–Dindo complications ≥grade III. A cut-off value of 27.3% for ∆-albumin on POD 1/2 predicted postoperative high-grade morbidity (sensitivity 75% and specificity 69%). The product of ∆-albumin and CRP on POD 4/5 identified patients with major complications more reliably than ∆-albumin or CRP alone (sensitivity 91% and specificity 72%). Conclusion . Preoperatively, albumin was a marker for nutritional status even if an inflammatory component was present. Postoperatively, ∆-albumin on POD 1/2 predicted high-grade morbidity. A new marker to identify patients with major complications on POD 4/5 is presented.